2020
DOI: 10.1159/000509853
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness, Safety, and Health-Related Quality of Life of Chronic Migraine Patients Treated with Onabotulinum Toxin A

Abstract: The present study aims to describe the efficacy and safety of onabotulinum toxin A (BonT-A) with evaluation of treatment satisfaction and impact on quality of life in chronic migraine (CM) patients in real life. Methods: This study was conducted in CM patients who were treated with BoNT-A with 12 months of follow-up. Data about outcome, adverse events, and patients' pre-and post-treatment status including health-related quality of life data were analyzed. Health-related quality of life scores were measured at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Results of a population-based study indicated that pain intensity, disability and headache frequency were correlated with quality of life scores ( p < 0.001) [ 61 ]. Beckman et al reported that decreased headache days after ONA treatment were correlated with increased quality of life in chronic migraine patients [ 39 ]. It seems that the decrease in the intensity of headache and neck pain, migraine and neck disability, and the number of days with headaches may increase the quality of life of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of a population-based study indicated that pain intensity, disability and headache frequency were correlated with quality of life scores ( p < 0.001) [ 61 ]. Beckman et al reported that decreased headache days after ONA treatment were correlated with increased quality of life in chronic migraine patients [ 39 ]. It seems that the decrease in the intensity of headache and neck pain, migraine and neck disability, and the number of days with headaches may increase the quality of life of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…The disability and pain experienced can affect daily work, family and social life, causing patients to try to find solutions to their problems [ 29 ]. The literature studies have shown reductions in migraine-related pain intensity and monthly migraine headache days and improvements in disability and quality of life outcomes with ONA treatment [ 37 , 38 , 39 ]. However, it is seen that there are no results after ONA treatment related to neck pain and disability in patients with CM and NP.…”
Section: Introductionmentioning
confidence: 99%